Training of Realistic Mathematics Education Learning Approach in Salawu Village - Afriansyah, Ekasatya Aldila; Nuraeni, Reni; Puspitasari, Nitta; Sundayana, Rostina; Jejen, Jejen; Sumia, Sumia; Damayanti, Desi; Lesmana, Andi (Indonesian Journal of Community Empowerment (IJCE), 2023)
This training activity is part of the service program of the lecturers of the Indonesian Education Institute. Salawu Village is a destination for IPI Garut mathematics education teachers according to the needs in the field of education in the knowledge of new learning innovations. We offer Indonesian Realistic Mathematics Education (PMRI) as learning that can be applied in schools around Salawu, especially elementary school. The purpose of this service is to provide training to teachers in Salawu village about PMRI. The service method used is the method of community education, consultation, and training that involves demonstrations. Data on community service activities including photos of activities, answers to questionnaires and questions by participants. The number of participants who attended 25 people consisting of elementary school teachers and prospective PLP student candidates for teacher candidates in Salawu village. The result of this training is PMRI which can be well translated and can be applied by the teacher in his class immediately.